Incidence of antepartum haemorrhage in pregnancy and its maternal-fetal outcome in admitted antenatal patients in tertiary care centre, Bhilai Durg, Chhattisgarh - Khandasu, Seema; Singh, Pooja; Ratnani, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Antepartum haemorrhage has always been one of the deadliest complications in obstetrics. Antepartum haemorrhage (APH) complicates about 2-5% of pregnancies. Maternal and perinatal morbidity and mortality associated with APH can be reduced significantly by aggressive expectant management. The present study was conducted to assess maternal and fetal outcome in patients with antepartum haemorrhage. Aims and objectives were to study the incidence of antepartum haemorrhage at SSIMS hospital. To highlight the importance of early diagnosis and treatment. To study the maternal and fetal outcome in antepartum haemorrhage. To study the associated risk factors contributing to maternal and fetal morbidity and mortality. Methods: The study was conducted in Shri Shakaracharya Institute of Medical Sciences, Bhilai, Durg, Chhattisgarh during the period of January 2020 to December 2020 after getting approval from the institutional ethical committee. 31 cases of APH with gestational age ≥28 weeks were included. They were distributed according to type of APH into abruptio placentae (AP), placenta previa (PP). Causes of APH were noted and maternal as well as perinatal outcome observed. Results: In the present study it was observed that incidence of APH was 2% out of 1503 deliveries. Out of 31 cases, 54.83% was AP followed by PP 45.16%. Abruption was the commonest cause of APH with its associated maternal morbidity and perinatal mortality and morbidity. Anemia was the most common complication in APH. Prematurity of the neonate was a serious complicating factor in APH. No maternal mortality was seen in this study. Conclusions: Overall incidence of APH has remained high. Though maternal morbidity is reduced with modern management of APH, but timely diagnosis and intervention is necessary. Perinatal morbidity can be reduced with good neonatal intensive care facilities.